Martin Heidegger's principle of identity: On belonging and Ereignis. Issue 3 (1st September 2017) - Griffiths, Dominic
Abstract : This article discusses Martin Heidegger's interpretation of Parmenides given in his last public lecture "The Principle of Identity" in 1957. The aim of the piece is to illustrate just how original and significant Heidegger's reading of Parmenides and the principle of identity is, within the history of philosophy. Thus the article will examine the traditional metaphysical interpretation of Parmenides, and consider G. W. F. Hegel and William James' account of the principle of identity in light of this. It will then consider Heidegger's contribution, his return to and re-interpretation of Parmenides in his last lecture. Heidegger will, through the Parmenidean claim that "Thinking and Being are one", deconstruct the traditional metaphysical understanding of the principle of identity, and in its place offer a radically different conception of how our relationship, our "belonging together" with Being can be understood.